IMPLEMENTATION AND EDUCATION OF GOODS RECORDING USING THE MICROSOFT ACCESS APPLICATION - Johny Budiman; Arianto Arianto (Universitas Internasional Batam, 2022)
Microsoft Access is one of application that can be managed to be a simple inventory application. The implementer of this community dedication managed to use this simple application into inventory application for PT Asia Foundry & Engineering with the intention of reducing inventory lost for 50% from before the company recognized this application. This analysis study is using observation and interview to find out the company’s background and problems and training for more knowledge about the application. With this inventory application in the form of Microsoft Access, then the problems faced by company can be minimized as promised and providing encouragement for the company to system information as the 4.0 industry revolution.